2014
DOI: 10.1289/ehp.1307081
|View full text |Cite
|
Sign up to set email alerts
|

Association between Source-Specific Particulate Matter Air Pollution and hs-CRP: Local Traffic and Industrial Emissions

Abstract: Background: Long-term exposures to particulate matter air pollution (PM2.5 and PM10) and high traffic load have been associated with markers of systemic inflammation. Epidemiological investigations have focused primarily on total PM, which represents a mixture of pollutants originating from different sources.Objective: We investigated associations between source-specific PM and high-sensitive C-reactive protein (hs-CRP), an independent predictor of cardiovascular disease.Methods: We used data from the first (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 33 publications
(42 reference statements)
10
49
2
3
Order By: Relevance
“…In our study area the decreasing west-to-east gradient mirrors the distribution of industrial locations, e.g., metallurgical-industry and Europe's largest inland harbour in Duisburg, located to the west of the study area (Figure 1), as well as transported emissions from other countries in the west of study area, e.g., the Netherlands or Great Britain. The decreasing north-to-south gradient on the other hand is consistent with the population density and the location of major arterial roads within our study area [32]. NO 2 concentrations estimated by EURAD-CTM showed an overall decrease between 2001 with 42.2 µg/m 3 and 2008 with 37.7 µg/m 3 , while a change between the ESCAPE-LUR and the back-extrapolated ESCAPE-LUR was not observed.…”
Section: Comparison Of Residence-based Eurad-ctm and Escape-lursupporting
confidence: 88%
See 2 more Smart Citations
“…In our study area the decreasing west-to-east gradient mirrors the distribution of industrial locations, e.g., metallurgical-industry and Europe's largest inland harbour in Duisburg, located to the west of the study area (Figure 1), as well as transported emissions from other countries in the west of study area, e.g., the Netherlands or Great Britain. The decreasing north-to-south gradient on the other hand is consistent with the population density and the location of major arterial roads within our study area [32]. NO 2 concentrations estimated by EURAD-CTM showed an overall decrease between 2001 with 42.2 µg/m 3 and 2008 with 37.7 µg/m 3 , while a change between the ESCAPE-LUR and the back-extrapolated ESCAPE-LUR was not observed.…”
Section: Comparison Of Residence-based Eurad-ctm and Escape-lursupporting
confidence: 88%
“…These observations indicate that EURAD-CTM and ESCAPE-LUR do not represent identical aspects of air pollution: while EURAD-CTM represents an area average similar to urban background concentrations, the ESCAPE-LUR was designed to predominantly estimate variability in local traffic-related air pollution, leading to a comparatively high correlation with local traffic-specific air pollution concentrations modeled by EURAD-CTM. The very low correlation with local industry-specific air pollution concentration at the residences indicates, that ESCAPE-LUR represents industry rather poorly compared to EURAD-CTM, where the overall spatial distribution (Figure 3) is mainly driven by industrial sources as has been observed in a previous study [32]. …”
Section: Source-specific Eurad-ctmmentioning
confidence: 53%
See 1 more Smart Citation
“…The results of the ESCAPE and HNR studies show linear exposure-effect relationships (20,21,29,31). Also, the associatons between particulate matter and the health sequelae listed above also occur beneath the currently valid European thresholds for particulate matter concentrations (20,21).…”
Section: Discussionmentioning
confidence: 90%
“…By contrast, the effect estimate decreases slightly when evaluating coronary events. Further results from the HNR study indicate a correlation between long-term concentrations of particulate matter at the home and high-sensitivity C-reactive protein (CRP) levels in serum (28,29), arterial blood pressure (30), and the degree and progression of intima-media thickness of the common carotid artery (a measure for subclinical atherosclerosis) (31,32). In addition, proximity to busy streets was associated with the degree of coronary artery calcification as measured with electron beam computed tomography (32).…”
Section: Discussionmentioning
confidence: 99%